PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATERI EKSTRAKSI DAN ISOLASI SENYAWA METABOLIT SEKUNDER DAUN BUAS-BUAS (Premna serratifolia Linn) DI PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - Endang Titi Rahayu; Dini Hadiarti; Tuti Kurniati (Universitas Muhammadiyah Pontianak, 2018)
Students’ difficulties in understanding the Extraction and Isolation of secondary metabolite compound of (Premna serratifolia Linn) are mainly caused by the improper learning media used by the teacher. By far, the media used in learning hasn’t met the students’ needs as it didn’t present the real process of Extraction and Isolation. This study aimed at developing a valid and a practical learning media. Using 3-D (Define, Design, Develop) model, this study employed questionnaire, interview, direct communication, and measurement as the data collection techniques. The data collection tools were interview guidance, observation sheet, and questionnaire sheet. The results of the validation from material, media, and language experts showed 93,9% valid. Whereas, the results of the practicality from individual try-out was 95,33%, and from small group try-out was 86,39%, and it’s regarded practical. In conclusion, the learning video of Extraction and Isolation of secondary metabolite compound of (Premna serratifolia Linn) is considered valid and practical. Therefore, it is recommended to be used in teaching learning process.Keywords: Extraction, Isolation, Developing 3-D Model, learning video